A six-week force-velocity profile based training is effective to optimize jump and change of direction performance in elite table tennis players - Conceição, F.; Neves, J.; Baena-Raya, A. (European Journal of Human Movement, 2024)
The aim of this study was to evaluate whether a specific training program based on the individual force-velocity (FV) profile would decrease the FVimb (i.e., difference between the players` actual and optimal profile) and, in turn, improve countermovement jump (CMJ) and change of direction (COD) performance. Nine elite table tennis players were assessed in two sessions for the FV profile, CMJ and COD. All players underwent a six-week specific resistance training program. The FVimb was significantly reduced (ES = -1.37; [95% confidence interval (CI) = -2.40; -0.35], p<0.05), with moderate changes observed for the theoretical maximal force (i.e., F0) (ES = 1.09; [95% CI = 0.10; 2.08], p<0.05) and velocity (i.e., V0) (ES = -0.96; [95% CI = -1.93; 0.02], p<0.05). Conversely, the maximal power output (i.e., Pmax) remained unchanged (p = 0.52). We also observed a significant CMJ enhancement (+15.31%) and a better COD performance (+5.09%). These findings suggest that assessing the FV profile might help coaches to individualize RT interventions. Specifically, increasing F0 values during jumping could be associated with enhanced CMJ and COD performance in elite table tennis with a force-deficit.